The Solvatofluorochromism of 2,4,6-Triarylpyrimidine Derivatives - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Rodríguez-Aguilar, J; Pastenes, C (Blackwell Publishing Inc., 2018)
Seven new 2,4,6-triarylpyrimidines were synthesized and their solvatofluorochromism investigated in 12 solvents and in an aqueous micellar solution of reduced Triton X-100. A multiparametric analysis of their emission band showed that the solvent dipolarity and basicity were mainly responsible for their solvatofluorochromism, which arose from an internal charge-transfer from a donor fragment to the pyrimidine acceptor, confirmed by theoretical calculations. In the micellar system, quenching of their fluorescence by addition of derivatives of 2,2,6,6-tetramethylpiperidinoxyl (TEMPO) radical was investigated and the results were consistent with the spectral changes brought about by the micro-heterogeneous system. © 2018 The American Society of Photobiology